Staphylococcus aureus enterotoxin B challenge of monkeys: correlation of plasma levels of arachidonic acid cascade products with occurrence of illness. - Jett, M (1990)
Arachidonic acid cascade products have been shown to be increased in vitro in Staphylococcus aureus enterotoxin B (SEB)-treated epithelial cell cultures in our laboratory. In order to confirm that these products were clinically related to SEB intoxication, monkeys were administered SEB by nasogastric intubation. It caused emesis in five of six monkeys (less than 4 h), and the sixth monkey showed signs of mild illness. The monkeys which vomited continued to display signs of gastrointestinal illness beyond 8 h but were without any apparent signs of illness by 24 h. Blood samples were collected prior to SEB administration, upon first indication of illness, and at twice that time interval. One week prior to SEB treatment, the same monkeys were administered saline by nasogastric intubation and in every way handled similarly in order to serve as their own controls. Blood samples were taken from the control animals at 0, 4, and 8 h. The plasma concentrations of prostaglandin E2 (PGE2), leukotriene B4 (LTB4), and 5-hydroxyeicosatetraenoic acid (5-HETE) did not vary significantly throughout the 8-h experiment for saline-treated controls, nor did they differ from the concentrations found in the plasma of monkeys just before administration of SEB. When the SEB-treated monkeys showed the first indication of illness (less than 4 h), the mean of the concentration in plasma of PGE2 increased 1.44-fold, that of LTB4 increased 2.23-fold, and that of 5-HETE was essentially unchanged. At twice the time interval of the first display of illness (less than 8 h), PGE2 was still elevated (1.48-fold), LTB4 had decreased slightly to 1.66-fold, and 5-HETE had soared (3,45-fold), suggesting a divergence in the enzymatic utilization of the parent compound of the latter two metabolites, 5-hydroperoxyeicosatetraenoic acid. These studies suggest that arachidonic acid cascade metabolites were a consequence of SEB intoxication and may provide a logical site for metabolic interference in SEB-induced toxicity.